Implementing Repetition Technique to Improve Students Vocabulary Mastery for Seventh Grade Students - Shofiatul Kholida; Silviana Qomariyah; Siti Aisa; Siti Fadilah Ulfa; Syami Abdul; Uswah Hasanah; Wahidah Isnanti; Wardatul Firdausiyah (Educazione: Journal of Education and Learning, 2024)
The researcher found the problems in the learning process that the students are lack of self-confidence, it makes them are unable to memorize, and difficult in pronouncing the words. Therefore, the researcher interest to research this repetition technique on students vocabulary mastery to strengthen their memory in mastering the vocabularies they learn without memorizing in the class. Vocabulary mastery is a complete skill to understand the stock of words and their meanings of a particular language. Repetition technique is repeated encounter of the words, the learners are enabled to retrieve the meaning or the form of the words to use them creatively. This research aims to know the effect of repetition technique on students vocabulary mastery. This research was conducted by using Classroom Action Research (CAR). In this study researcher made VII A students of SMP Insan Terpadu as the research target, which consist of 13 male students in academic year 2022/2023.The data were gathered through qualitative data and quantitative data. The qualitative data were gained by observation. Then, quantitative data were obtained from the student’s vocabulary score of pre-test and post-test. In this research, the researcher used 1 cycle, because based on the results, it showed that there was a development on students vocabulary mastery. It can be seen from the mean score of pre-test which was 58, while the mean score of post-test was 82. Hence, the criteria of success were achieved. Furthermore, the results of the observation showed that the students were interested in the lesson and they able to master the vocabulary with four criteria success in the teaching learning process during the implementation of repetition technique.